Perfect Match? The Practice Ecology of a Labor Market Initiative for Refugees - Berthou, Sara Kristine Gløjmar; Buch, Anders (Nordic Journal of Working Life Studies, 2018)
The article investigates the case of a Danish labor market initiative for refugees with a professional engineering background. The ambition is to identify the causes and contextual elements that are active in shaping labor market initiatives directed at groups of refugees. Contemporary theories of practice are used to investigate the structures that enable, constrain, and channel the activities related to the initiative. The discussion focuses on the practice of the initiative in order to analyze ways in which activities are organized in the site. Furthermore, it sets out to investigate how the practices exist and are interconnected in ecological arrangements where practice architectures hold one another in place. The theoretical conceptualization in terms of practice, practices, practice architectures, and practice ecologies helps to explain how a seemingly ideal initiative turned out to have a little impact in bringing the refugee engineers closer to employment on the Danish labor market.